Kebijakan Daerah Dalam Perlindungan Sosial bagi Pekerja Rentan: Local Policy Roles in Protecting Social Security for Vulnerable Workers - Yudha Andriyanto; Willar Haruman; Endah Pujiastuti (Universitas Semarang, 2025)
This study analyzes the exercise of authority by the Semarang City Government in providing employment social security protection for vulnerable workers including farmers, fishermen, parking attendants, and other informal sector workers, and develops responsive legal solutions to address the constraints that hinder effective implementation. Departing from earlier studies that focus primarily on national level regulation or abstract justice theories, this research presents novelty by combining an empirical evaluation of local policy performance with the analytical frameworks of Development Law Theory, Social Justice Theory, Policy Implementation Theory, Responsive Law, and Good Governance principles. Employing a socio legal method with a statute approach, the study draws on interviews, field observations, and document analysis involving vulnerable workers, the Manpower Office, and BPJS Ketenagakerjaan. The findings show that employment social security coverage reaches only fifteen percent of vulnerable workers due to the absence of specific local regulation, procedural rigidity within administrative systems, weak coordination among institutions, and limited public awareness and outreach. The study recommends the formulation of a dedicated Local Regulation, the simplification of registration procedures, the provision of subsidized contributions for vulnerable worker groups, and the establishment of a tripartite governance forum to enhance institutional capacity and ensure more effective welfare protection within Semarang City. Penelitian ini menganalisis pelaksanaan kewenangan Pemerintah Kota Semarang dalam memberikan perlindungan jaminan sosial ketenagakerjaan bagi pekerja rentan yang meliputi petani, nelayan, juru parkir, dan pekerja sektor informal lainnya, serta merumuskan solusi hukum yang responsif untuk mengatasi berbagai kendala yang menghambat efektivitas implementasi. Berbeda dari penelitian sebelumnya yang terutama berfokus pada regulasi tingkat nasional atau teori keadilan yang bersifat abstrak, penelitian ini menawarkan kebaruan melalui penggabungan evaluasi empiris terhadap kinerja kebijakan daerah dengan kerangka analitis Teori Hukum Pembangunan, Teori Keadilan Sosial, Teori Implementasi Kebijakan, Hukum Responsif, dan prinsip Tata Kelola Pemerintahan yang Baik. Dengan menggunakan metode socio legal melalui pendekatan perundang-undangan, penelitian ini menghimpun data melalui wawancara, observasi lapangan, dan analisis dokumen yang melibatkan pekerja rentan, Dinas Ketenagakerjaan, dan BPJS Ketenagakerjaan. Temuan penelitian menunjukkan bahwa cakupan perlindungan jaminan sosial ketenagakerjaan baru mencapai lima belas persen dari total pekerja rentan akibat ketiadaan regulasi daerah yang khusus mengatur perlindungan pekerja rentan, rigiditas prosedur administratif, lemahnya koordinasi antar lembaga, serta keterbatasan sosialisasi dan literasi publik. Penelitian ini merekomendasikan penyusunan Peraturan Daerah khusus, penyederhanaan prosedur pendaftaran, pemberian subsidi iuran bagi kelompok pekerja rentan, serta pembentukan forum tata kelola tripartit untuk memperkuat kapasitas kelembagaan dan memastikan perlindungan kesejahteraan yang lebih efektif bagi pekerja rentan di Kota Semarang.